Unencumbered by style: Why do funds change factor loadings and does it help? - Ting Bai; Jens Hilscher; Anna Scherbina (American Enterprise Institute (AEI), 2024)
We show that active equity funds deliberately alter their factor loadings rather than maintaining a constant style. Changes are larger following quarters in which funds either under- or out-perform other funds based on returns or fund flows. Motivated by this observation, we identify a new measure of manager skill, which we call "tactical investment skill." It captures a manager's ex-ante observable ability to increase future returns through loadings changes. We show that high-skill managers outperform their low-skill peers in the following month in terms of raw returns and alphas. This outperformance is more pronounced following quarters with large loadings changes.
Keywords: G10; G20; G23; 330; Mutual fund style; style changes; active fund management; manager skill; factor timing; tactical investment skill